IMPROVING THE ACCOUNTING AND AUDITING OF LIABILITIES IN COMMERCIAL BANKS - Alimova Qizlarxon Tura qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The reliability of financial reporting in commercial banks largely depends on the accuracy and transparency of liability accounting and auditing. Liabilities constitute a significant portion of bank balance sheets and directly influence liquidity, solvency, and financial stability. This study aims to analyze the methodological aspects of liability auditing in commercial banks and propose approaches to improve audit effectiveness under modern financial conditions. The research applies analytical, comparative, and systematic methods to evaluate existing audit practices and international experience. The results demonstrate that risk-based auditing, digital audit tools, and enhanced internal control assessment significantly improve the quality of liability audits. The study concludes with recommendations aimed at strengthening audit procedures and improving financial reporting reliability in commercial banks.